Relationship Between Cyclic Citrullinated Peptide Antibodies Positivity and HLA-DRB1 Shared Epitope Alleles in Patients with Rheumatoid Arthritis in Turkey - İdris Dayan,; Canan Tıkız,; Fatma Taneli,; Cevval Ulman,; Gürol Ulutaş,; Çiğdem Tüzün, (Archives of Rheumatology, 2010)
Objective: The most characteristic genetic risk factors for rheumatoid arthritis (RA), the HLA-DRB1 shared epitope (SE) alleles, encode for a common amino acid sequence in the peptide-presenting part of the HLA class II molecule. These SE alleles have been described recently to be a risk factor for the development of antibodies against citrullinated proteins in RA. The current study was performed to investigate the association between the cyclic citrullinated peptide antibodies (anti-CCP) and HLA-DR1 HLA-DRB1 shared epitope alleles in patients with RA in Turkey. Materials and Methods: Sixty patients with RA who were newly diagnosed or under conventional treatment in our clinic and 60 healthy volunteers as controls were enrolled in the study. In patients with RA anti-CCP levels were investigated with enzyme-linked immunosorbent assay and HLA-DRB1 subtyping and SE was assessed by polymerase chain reaction. Only anti-CCP was measured in healthy volunteers. Results: SE was positive in 50% of the patients with RA. Amongst the SE carriers, 30% of them were carrying double copy of SE. While anti-CCP was positive in 73,3% of patients with RA, this ratio was 0% in healthy volunteers. We determined that the existence of SE increases the positivity of anti-CCP (OR=4,3, 95% [CI], P=0.04 ), and a significant relationship was found between the anti-CCP positivity and the RF positivity. (OR=5,3, 95% [CI] P<0.05). Conclusion: The results of the present study revealed that Turkish patients with RA carrying SE with HLA-DRB1 genes is significantly related with the production of anti-CCP. The diagnostic sensitivity and specificity of anti-CCP for RA is determined as 73,3% and 100% respectively. (Turk J Rheumatol 2010; 25: 12-8)